Molecular cloning of IGλ rearrangements using long‐distance inverse PCR (LDI‐PCR). (4th December 2012) - Shimanuki, Masaya; Sonoki, Takashi; Hosoi, Hiroki; Watanuki, Jyuri; Murata, Shogo; Kawakami, Keiki; Matsuoka, Hiroshi; Hanaoka, Nobuyoshi; Nakakuma, Hideki
Abstract Objectives Malignant cells of mature B‐cell origin show tumor‐specific clonal immunoglobulin gene (IG) rearrangements, including V(D)J recombinations, nucleotide mutations, or translocations. Rapid molecular cloning of the breakpoint sequence by long‐distance inverse PCR (LDI‐PCR) has so far been applied to rearrangements targeted to IGH joining, IGH switch, and IGκ regions. We tended to apply LDI‐PCR method for cloning of IGλ rearrangements. Methods To identify which IGλ isotype segment was rearranged, we performed Southern blot analysis using isotype‐specific probes. We set inverse primers on the telomeric side of each joining region and amplified rearranged bands detected by Southern blot analysis as corresponding PCR products. Results All germline IGλ segments were successfully amplified as expected PCR products. We determined breakpoint sequences of five chromosome translocations involving IGλ locus: three novel t(8;22)(q24;q11), one known t(3;22)(q27;q11), and one partially known t(11;22)(q13;q11). Two of the three t(8;22)(q24;q11) were involved in Jλ with a recombination signal sequence and one of three in the first exon of IGLL5, which lies upstream of Jλ1. Three 8q24 breakpoints were widespread at 132, 260 and 366 kb downstream of MYC locus. The t(3;22)(q27;q11) showed a juxtaposition of Jλ2 and the first intron of BCL6, as previously reported. In t(11;22)(q13;q11), 3′UTR of cyclin D1 fused to the constant region of λ7 with nucleotide mutations. We also amplified four Vλ/Jλ recombination sequences. Conclusion Our method is a useful tool for molecular analysis of genetic events in IGλ.